Low-smoke halogen-free polyolefin insulating layer fireproof cable

By using a multi-layer structural design of modified polyethylene insulation layer, mineral fireproof layer and low-smoke halogen-free sheath in low-smoke halogen-free cable, the problem of difficult balance between flame retardancy and mechanical properties of existing cables is solved. , achieving the effects of efficient flame retardant, low smoke emissions and excellent mechanical properties.

CN119480246AInactive Publication Date: 2025-02-18SICHUAN CHAODA CABLE MFG CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411593343.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing low-smoke halogen-free cables are difficult to balance between achieving high flame retardancy and excellent mechanical properties and heat resistance. In addition, traditional halogen materials release toxic smoke when burning, which poses environmental protection and safety risks.

Method used

The polyolefin insulating layer consisting of modified polyethylene and ethylene-vinyl acetate copolymer is combined with mineral fireproof layer of magnesium hydroxide, aluminum hydroxide, kaolin and glass fiber, as well as polyolefin elastomer and polypropylene blend, The low-smoke halogen-free sheath of nanoscale magnesium hydroxide and expanded flame retardant improves the flame retardant performance and mechanical strength of the cable through multi-layer structural design and material combination.

Benefits of technology

It achieves excellent flame retardant performance and excellent mechanical properties with low smoke and environmental protection, which can effectively suppress flame spread under high temperature conditions, reduce smoke emissions, and improve the overall performance and safety of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480246A_ABST
    Figure CN119480246A_ABST
Patent Text Reader

Abstract

The invention discloses a low-smoke halogen-free polyolefin insulating layer fireproof cable. According to the low-smoke halogen-free sheath fireproof cable disclosed by the invention, excellent flame retardant property and low-smoke emission characteristic are realized by optimizing a multi-layer structural design and selecting specific material combination. The polyolefin insulating layer adopts the combination of modified polyethylene and EVA (Ethylene Vinyl Acetate), so that the elasticity and the thermal stability of the cable are enhanced; through the synergistic effect of magnesium hydroxide, aluminum hydroxide, kaolin and glass fibers, the flame retardant property and the mechanical strength of the mineral fireproof layer are remarkably improved; the polyolefin elastomer, the polypropylene blend, the nanoscale magnesium hydroxide and other materials in the low-smoke halogen-free sheath provide excellent low-smoke and environment-friendly flame-retardant effects, and meanwhile, the durability and the structural stability of the cable are kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of fireproof cables, and in particular relates to a low-smoke halogen-free polyolefin insulation layer fireproof cable. Background Art

[0002] With the increasing safety requirements for cable materials in public places and industrial applications, traditional cable materials often use halides to improve flame retardancy. Although these halides can effectively inhibit the spread of flames when burning, they will release a large amount of toxic smoke and corrosive gases, which not only pose a threat to personnel health, but may also damage equipment and building structures. Therefore, with increasingly stringent fire protection and environmental protection requirements, this traditional solution is gradually considered unsustainable. In order to solve this problem, low-smoke halogen-free cables have gradually become a hot spot for research and application. They are designed to achieve high-efficiency flame retardancy through halogen-free materials, while only releasing a small amount of non-toxic smoke when burning, reducing harm to personnel and the environment. However, the current low-smoke halogen-free cables still face challenges in terms of performance, especially in achieving a balance between high flame retardancy and excellent mechanical properties and heat resistance. There is still room for improvement, and it is necessary to further improve its comprehensive performance through material innovation and multi-layer structure design to meet increasingly stringent safety and environmental standards.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a low-smoke, halogen-free polyolefin insulated fireproof cable, which solves the problems raised in the above-mentioned background technology.

[0005] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:

[0006] A low-smoke halogen-free polyolefin insulated layer fireproof cable, comprising a low-smoke halogen-free sheath and a plurality of cables, the cables comprising an annealed stranded copper conductor, a polyolefin insulation layer, and a mineral fireproof layer wound in sequence from the inside to the outside, a filling layer is arranged inside the low-smoke halogen-free sheath, and the cables are located inside the filling layer;

[0007] Wherein, the polyolefin insulation layer is composed of modified polyethylene and ethylene-vinyl acetate copolymer;

[0008] The mineral fireproof layer is composed of magnesium hydroxide, aluminum hydroxide, kaolin and glass fiber;

[0009] The low smoke halogen-free sheath is made of a mixture of polyolefin elastomer, polypropylene blend, nano-grade magnesium hydroxide, intumescent flame retardant and calcium carbonate.

[0010] Optionally, the method for preparing the polyolefin insulation layer comprises the following steps:

[0011] Weigh polyethylene, ethylene-vinyl acetate copolymer, dicumyl peroxide as an initiator, and an antioxidant;

[0012] Mixing polyethylene, EVA and DCP, and melt blending at a temperature of 170-190° C. for 15-20 minutes, with a mixer speed of 32-35 rpm, to ensure that polyethylene and EVA are chemically cross-linked to form a modified polyolefin;

[0013] After the reaction is completed, the mixture is cooled to 25-30°C and granulated to make the modified polyolefin material into particles for subsequent processing;

[0014] The granulated modified polyolefin material is fed into an extruder and processed at an extrusion temperature of 200-250°C, uniformly coated on the outer surface of the copper conductor to form an insulating layer, and finally the extruded insulating layer is cured at a temperature of 150-180°C for 30-60 minutes.

[0015] Optionally, the mass fraction of polyethylene is 100-130 parts, the mass fraction of ethylene-vinyl acetate copolymer is 20-30 parts, the mass fraction of dicumyl peroxide is 1-2 parts, and the mass fraction of antioxidant is 1-3 parts.

[0016] Optionally, the method for preparing the mineral fireproof layer comprises the following steps:

[0017] Magnesium hydroxide, aluminum hydroxide and kaolin were selected as flame retardant fillers, while glass fiber was added to enhance the mechanical properties of the layer;

[0018] In a mixing device, magnesium hydroxide, aluminum hydroxide, kaolin and glass fiber are uniformly mixed, and the mixing temperature is controlled at 100-130°C for 15-20 minutes;

[0019] The mixture is extruded through a twin-screw extruder at a temperature of 160-200°C to form a uniform mineral fireproof layer, and the screw speed of the extruder is controlled at 100-120rpm;

[0020] The extruded mineral fireproof layer is evenly coated on the outside of the insulation layer of the cable. The layer thickness is maintained between 2-4 mm to provide effective flame retardant protection. The coated fireproof layer is cured at 150°C for 30-45 minutes and then cooled to room temperature.

[0021] Optionally, 30-40 parts of magnesium hydroxide, 15-25 parts of aluminum hydroxide and 20-30 parts of kaolin are weighed as flame retardant fillers, and 5-10 parts of glass fiber are added to enhance the mechanical properties of the layer.

[0022] Optionally, the preparation method of the low smoke zero halogen sheath is:

[0023] Weigh polyolefin elastomer, polypropylene blend, nano-magnesium hydroxide, intumescent flame retardant, and calcium carbonate;

[0024] Mix the above raw materials in a high-speed mixer at a temperature of 80-100°C for 10-15 minutes to ensure uniform dispersion and initial combination of the materials;

[0025] The mixed material is fed into a twin-screw extruder and extruded and granulated at a temperature range of 250-300°C, with the screw speed set at 120-150rpm to form particles;

[0026] The granulated material is extruded again through an extruder at a temperature of 200-250° C. to form a sheath with a thickness of 3 mm.

[0027] Optionally, the mass fraction of polyolefin elastomer is 100-120 parts, the mass fraction of polypropylene blend is 30-50 parts, the mass fraction of nano-magnesium hydroxide is 20-30 parts, and the mass fraction of intumescent flame retardant is 5-10 parts, and the mass fraction of calcium carbonate added is 15-20 parts.

[0028] Optionally, the number of cables is 4-6. When preparing the cable, first, a mineral insulation layer, an insulating isolation layer, and a mineral fireproof layer are sequentially coated on the outer surface of the annealed stranded copper conductor to obtain a cable core; then, a filling layer is formed on the outer surface of multiple cable cores; finally, a low-smoke halogen-free outer sheath is coated on the outer surface of the filling layer.

[0029] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time:

[0030] The low-smoke halogen-free sheathed fireproof cable of the present invention achieves excellent flame retardant performance and low smoke emission characteristics by optimizing the multi-layer structure design and selecting a specific material combination. The polyolefin insulation layer adopts a combination of modified polyethylene and EVA to enhance the elasticity and thermal stability of the cable; the mineral fireproof layer significantly improves the flame retardant performance and mechanical strength through the synergistic effect of magnesium hydroxide, aluminum hydroxide, kaolin and glass fiber; the polyolefin elastomer, polypropylene blend and nano-grade magnesium hydroxide in the low-smoke halogen-free sheath provide low smoke, environmentally friendly and excellent flame retardant effects, while maintaining the durability and structural stability of the cable.

[0031] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The drawings described below are only some embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0033] In the figure:

[0034] Figure 1 This is a schematic diagram of the three-dimensional structure of the insulation layer fire-resistant cable.

[0035] In the accompanying drawings, the components represented by the reference numerals are listed as follows:

[0036] 1. Copper conductor; 2. Polyolefin insulation layer; 3. Mineral fireproof layer; 4. Low smoke halogen-free sheath; 5. Filling layer.

[0037] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION

[0038] The present invention will now be described in further detail with reference to the accompanying drawings.

[0039] In this embodiment, a low-smoke halogen-free polyolefin insulated layer fireproof cable is provided, including a low-smoke halogen-free sheath and a plurality of cables, the cables including an annealed stranded copper conductor, a polyolefin insulation layer, and a mineral fireproof layer wound in sequence from the inside to the outside, a filling layer is arranged inside the low-smoke halogen-free sheath, and the cables are located inside the filling layer;

[0040] Wherein, the polyolefin insulation layer is composed of modified polyethylene and ethylene-vinyl acetate copolymer;

[0041] The mineral fireproof layer is composed of magnesium hydroxide, aluminum hydroxide, kaolin and glass fiber;

[0042] The low smoke halogen-free sheath is made of a mixture of polyolefin elastomer, polypropylene blend, nano-grade magnesium hydroxide, intumescent flame retardant and calcium carbonate.

[0043] In this embodiment, the method for preparing the polyolefin insulation layer comprises the following steps:

[0044] Weigh polyethylene, ethylene-vinyl acetate copolymer, dicumyl peroxide as an initiator, and an antioxidant;

[0045] Mixing polyethylene, EVA and DCP, and melt blending at a temperature of 170-190° C. for 15-20 minutes, with a mixer speed of 32-35 rpm, to ensure that polyethylene and EVA are chemically cross-linked to form a modified polyolefin;

[0046] After the reaction is completed, the mixture is cooled to 25-30°C and granulated to make the modified polyolefin material into particles for subsequent processing;

[0047] The granulated modified polyolefin material is fed into an extruder and processed at an extrusion temperature of 200-250°C, uniformly coated on the outer surface of the copper conductor to form an insulating layer, and finally the extruded insulating layer is cured at a temperature of 150-180°C for 30-60 minutes.

[0048] In this embodiment, the mass fraction of polyethylene is 100-130 parts, the mass fraction of ethylene-vinyl acetate copolymer is 20-30 parts, the mass fraction of dicumyl peroxide is 1-2 parts, and the mass fraction of antioxidant is 1-3 parts.

[0049] In this embodiment, the method for preparing the mineral fireproof layer comprises the following steps:

[0050] Magnesium hydroxide, aluminum hydroxide and kaolin were selected as flame retardant fillers, while glass fiber was added to enhance the mechanical properties of the layer;

[0051] In a mixing device, magnesium hydroxide, aluminum hydroxide, kaolin and glass fiber are uniformly mixed, and the mixing temperature is controlled at 100-130°C for 15-20 minutes;

[0052] The mixture is extruded through a twin-screw extruder at a temperature of 160-200°C to form a uniform mineral fireproof layer, and the screw speed of the extruder is controlled at 100-120rpm;

[0053] The extruded mineral fireproof layer is evenly coated on the outside of the insulation layer of the cable. The layer thickness is maintained between 2-4 mm to provide effective flame retardant protection. The coated fireproof layer is cured at 150°C for 30-45 minutes and then cooled to room temperature.

[0054] In this embodiment, 30-40 parts of magnesium hydroxide, 15-25 parts of aluminum hydroxide and 20-30 parts of kaolin are weighed as flame retardant fillers, and 5-10 parts of glass fiber are added to enhance the mechanical properties of the layer.

[0055] The preparation method of the low smoke zero halogen sheath in this embodiment is:

[0056] Weigh polyolefin elastomer, polypropylene blend, nano-magnesium hydroxide, intumescent flame retardant, and calcium carbonate;

[0057] Mix the above raw materials in a high-speed mixer at a temperature of 80-100°C for 10-15 minutes to ensure uniform dispersion and initial combination of the materials;

[0058] The mixed material is fed into a twin-screw extruder and extruded and granulated at a temperature range of 250-300°C, with the screw speed set at 120-150rpm to form particles;

[0059] The granulated material is extruded again through an extruder at a temperature of 200-250°C and evenly coated on the outer layer of the cable with a sheath thickness of 2-4 mm. After the coating is completed, the sheath is cooled to room temperature in a cooling device to solidify and shape it.

[0060] In this embodiment, the mass fraction of the polyolefin elastomer is 100-120 parts, the mass fraction of the polypropylene blend is 30-50 parts, the mass fraction of the nano-magnesium hydroxide is 20-30 parts, and the mass fraction of the intumescent flame retardant is 5-10 parts, and the mass fraction of calcium carbonate added is 15-20 parts.

[0061] In this embodiment, the number of cables is 4-6. When preparing the cable, first, a mineral insulation layer, an insulating isolation layer, and a mineral fireproof layer are sequentially coated on the outer surface of the annealed stranded copper conductor to obtain a cable core; then, a filling layer is formed on the outer surface of the plurality of cable cores; finally, a low-smoke halogen-free outer sheath is coated on the outer surface of the filling layer.

[0062] Embodiment 1:

[0063] The raw material ratio of the polyolefin insulation layer is 120 parts of polyethylene, 25 parts of ethylene-vinyl acetate copolymer (EVA), 1.5 parts of dicumyl peroxide (DCP), and 2 parts of antioxidant;

[0064] The raw material ratio of the mineral fireproof layer is 35 parts of magnesium hydroxide, 20 parts of aluminum hydroxide, 25 parts of kaolin, and 8 parts of glass fiber;

[0065] The raw material ratio of the low-smoke halogen-free sheath is 110 parts of polyolefin elastomer, 40 parts of polypropylene, 25 parts of nano-grade magnesium hydroxide, 8 parts of intumescent flame retardant, and 18 parts of calcium carbonate.

[0066] Embodiment 2:

[0067] Conductor and polyolefin insulation layer The conductor and insulation layer are prepared by the method in Example 1;

[0068] The raw material ratio of the mineral fireproof layer is 30 parts of magnesium hydroxide, 25 parts of aluminum hydroxide, 20 parts of kaolin, and 10 parts of glass fiber;

[0069] The raw material ratio of the low-smoke halogen-free sheath is 120 parts of polyolefin elastomer, 50 parts of polypropylene, 30 parts of nano-grade magnesium hydroxide, 10 parts of intumescent flame retardant, and 20 parts of calcium carbonate;

[0070] Embodiment 3:

[0071] The polyolefin insulation layer is consistent with that in Example 1;

[0072] The raw material ratio of the mineral fireproof layer is 40 parts of magnesium hydroxide, 15 parts of aluminum hydroxide, 30 parts of kaolin, and 5 parts of glass fiber;

[0073] The raw material ratio of the low-smoke halogen-free sheath is 100 parts of polyolefin elastomer, 30 parts of polypropylene, 20 parts of nano-grade magnesium hydroxide, 5 parts of intumescent flame retardant, and 15 parts of calcium carbonate.

[0074] Comparison example:

[0075] Ordinary annealed stranded copper conductors are used without additional insulation treatment. Ordinary polyethylene material is directly extruded and coated on the copper conductor, the extrusion temperature is set at 200℃, and the thickness is controlled at 2 mm. Magnesium hydroxide and calcium carbonate are evenly mixed in an ordinary mixer and coated on the outside of the insulation layer with a thickness of 2 mm and an extrusion temperature of 180℃. PVC or ordinary polyethylene is used as the filling layer, and then a conventional polyethylene and calcium carbonate mixture is used as the sheath material, which is coated at 200℃, and the sheath thickness is maintained at 2-3 mm. The entire cable structure is naturally cooled to room temperature without curing treatment.

[0076] The experimental procedure is to subject the prepared overall cables of each embodiment and control example to a standard flame retardant test. First, the cable sample is cut into a specified length and fixed vertically in an experimental device. The lower end of the sample is burned with a flame for a certain period of time (such as 30 seconds), and then the oxygen index (LOI) is recorded to measure the minimum oxygen concentration required for the material to maintain combustion. Next, the sample is subjected to a UL94 vertical combustion test to assess its flame retardant grade, and finally a smoke density test is performed under the ASTME662 standard, and the smoke concentration generated by the combustion is recorded by an optical density measuring device. All test steps are repeated three times in a controlled environment to ensure the reliability and consistency of the data. The experimental results are shown in the following table.

[0077]

[0078] As can be seen from the above table, inorganic flame retardants such as magnesium hydroxide and aluminum hydroxide are used in Examples 1-3. These materials will decompose and release moisture at high temperatures, and reduce the temperature of the cable surface through heat absorption, thereby inhibiting the spread of flames. At the same time, the addition of kaolin and glass fiber enhances the structural strength and heat resistance of the fireproof layer. When these fillers are combined together, they play a synergistic flame retardant role, that is, multiple flame retardant mechanisms work together to greatly improve the flame retardant effect of the material.

[0079] In the low smoke halogen-free sheath, the combination of polyolefin elastomer, nano-magnesium hydroxide and intumescent flame retardant further enhances the flame retardancy. Nano-magnesium hydroxide provides a larger surface area and better decomposition heat absorption performance, while the intumescent flame retardant forms a stable carbonized layer at high temperature to block the diffusion of flame and oxygen. The combined effect of polypropylene and calcium carbonate improves the mechanical strength and heat resistance of the sheath.

[0080] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.

Claims

1. A low-smoke halogen-free polyolefin insulated fireproof cable, characterized in that: The invention comprises a plurality of cables with a low-smoke halogen-free sheath (4), wherein the cables comprise an annealed stranded copper conductor (1), a polyolefin insulation layer (2), and a mineral fireproof layer (3) which are wound in sequence from the inside to the outside, a filling layer (5) is arranged inside the low-smoke halogen-free sheath (4), and the cables are located inside the filling layer (5); Wherein, the polyolefin insulation layer (2) is composed of modified polyethylene and ethylene-vinyl acetate copolymer; The mineral fireproof layer (3) is composed of magnesium hydroxide, aluminum hydroxide, kaolin and glass fiber; The low-smoke halogen-free sheath (4) is made by mixing polyolefin elastomer, polypropylene blend, nano-grade magnesium hydroxide, expansion type flame retardant and calcium carbonate.

2. A low-smoke halogen-free polyolefin insulated fireproof cable according to claim 1, characterized in that: The method for preparing the polyolefin insulation layer (2) comprises the following steps: Weigh polyethylene, ethylene-vinyl acetate copolymer, dicumyl peroxide as an initiator, and an antioxidant; Mixing polyethylene, EVA and DCP, and melt blending at a temperature of 170-190° C. for 15-20 minutes, with a mixer speed of 32-35 rpm, to ensure that polyethylene and EVA are chemically cross-linked to form a modified polyolefin; After the reaction is completed, the mixture is cooled to 25-30°C and granulated to make the modified polyolefin material into particles for subsequent processing; The granulated modified polyolefin material is fed into an extruder and processed at an extrusion temperature of 200-250° C. to be evenly coated on the outer surface of the copper conductor (1) to form an insulating layer. Finally, the extruded insulating layer is cured at a temperature of 150-180° C. for 30-60 minutes.

3. A low-smoke zero-halogen polyolefin insulated fireproof cable according to claim 1, characterized in that: The mass fraction of polyethylene is 100-130 parts, the mass fraction of ethylene-vinyl acetate copolymer is 20-30 parts, the mass fraction of dicumyl peroxide is 1-2 parts, and the mass fraction of antioxidant is 1-3 parts.

4. A low-smoke halogen-free polyolefin insulated fireproof cable according to claim 1, characterized in that: The method for preparing the mineral fireproof layer (3) comprises the following steps: Magnesium hydroxide, aluminum hydroxide and kaolin were selected as flame retardant fillers, while glass fiber was added to enhance the mechanical properties of the layer; In a mixing device, magnesium hydroxide, aluminum hydroxide, kaolin and glass fiber are uniformly mixed, and the mixing temperature is controlled at 100-130°C for 15-20 minutes; Extruding the mixture through a twin-screw extruder at a temperature of 160-200° C. to form a uniform mineral fireproof layer (3), wherein the screw speed of the extruder is controlled at 100-120 rpm; The extruded mineral fireproof layer (3) is evenly coated on the outer insulation layer of the cable, and the layer thickness is maintained between 2-4 mm to provide effective flame retardant protection. The coated fireproof layer is cured at 150°C for 30-45 minutes and then cooled to room temperature.

5. The low-smoke zero-halogen polyolefin insulated fireproof cable according to claim 1, characterized in that: 30-40 parts of magnesium hydroxide, 15-25 parts of aluminum hydroxide and 20-30 parts of kaolin are weighed as flame retardant fillers, and 5-10 parts of glass fiber are added to enhance the mechanical properties of the layer.

6. The low-smoke halogen-free polyolefin insulated fireproof cable according to claim 1, characterized in that: The preparation method of the low smoke zero halogen sheath (4) is as follows: Weigh polyolefin elastomer, polypropylene blend, nano-magnesium hydroxide, intumescent flame retardant, and calcium carbonate; Mix the above raw materials in a high-speed mixer at a temperature of 80-100°C for 10-15 minutes to ensure uniform dispersion and initial combination of the materials; The mixed material is fed into a twin-screw extruder and extruded and granulated at a temperature range of 250-300°C, with the screw speed set at 120-150rpm to form particles; The granulated material is extruded again through an extruder at a temperature of 200-250° C. to form a sheath with a thickness of 3 mm.

7. The low-smoke halogen-free polyolefin insulated fireproof cable according to claim 1, characterized in that: The mass fraction of the polyolefin elastomer is 100-120 parts, the mass fraction of the polypropylene blend is 30-50 parts, the mass fraction of the nano-magnesium hydroxide is 20-30 parts, the mass fraction of the intumescent flame retardant is 5-10 parts, and the mass fraction of the calcium carbonate added is 15-20 parts.

8. The low-smoke zero-halogen polyolefin insulated fireproof cable according to claim 1, characterized in that: The number of cables is 4 to 6. When preparing the cable, firstly, a mineral insulation layer, an insulation isolation layer, and a mineral fireproof layer (3) are sequentially coated on the outer surface of an annealed stranded copper conductor (1) to obtain a cable core; then, a filling layer (5) is filled on the outer surface of multiple cable cores; and finally, a low-smoke halogen-free outer sheath is coated on the outer surface of the filling layer (5).

Citation Information

Cited By

  • Multi-layer co-extrusion cable based on low-smoke halogen-free flame-retardant composite layer and preparation method of multi-layer co-extrusion cable

    CN120183780A